AIDS e infecção pelo HIV: métodos de ensino em questão - Calças, Ed Ganzaroli Pereira (2008)
The research has the objective to compare the results of learning about Aids and infection by Hiv considering the teaching job using the exhibition verbal method for a group of students and the elaboration on the whole method based on Piaget s epistemology for another group of students. For the performance of his work we use almost an experimental delineation. The dependent variable is represented by the students knowledge about Aids and Hiv and the independent variables are the two kinds of class based on the different methods. The procedures are separated in three stages: application of the same questionaire for the two groups before the classes, the intervention, in other words, the classes, and the reaplication of the same questionaire after the classes. At the moment of comparison of this evaluation before the classes and after the classes, within each group, we can realize that the two groups improved, however the second group had a better evolution than the first one. The comparison between the groups, we can see that it didn t have a significative difference that will be able to confirm the hypothesis that the elaboration on the whole method based on Piaget s constructivist epistemology is more efficient than the exhibition verbal method.